FETI Methods for the Simulation of Biological Tissues - Augustin, Christoph; Steinbach, Olaf (Domain decomposition methods in science and engineering XX. International Conference on Domain Decomposition Methods for Partial Differential Equations (20th : 2011 : San Diego, Calif.), 2013)
In this paper we describe the application of finite element tearing and interconnecting methods for the simulation of biological tissues, as a particular application we consider the myocardium. As most other tissues, this material is characterized by anisotropic and nonlinear behavior.